Rubble BricQ (Briket Limbah Daun Karet) Sebagai Inovasi Bahan Bakar Alternatif Masa Kini - Muhammad Sopyan Ismail; Aldi Nur Rahman; Aulia Hanna Farhatin; Malikhatun Khasanah; Diah Nugraheni (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2021)
Rubber leaf waste is often found in rubber plantations and is considered of no value to the community. Rubble BricQ (Rubber Leaf Waste Briquettes) is an innovative alternative fuel today by utilizing rubber leaf waste that does not pollute the environment and the price is affordable. Briquettes can replace some of the uses of kerosene and LPG gas such as food processing, drying, burning, and heating. The purpose of this study was to find out how to make Rubble BricQ (Rubber Leaf Waste Briquettes) as an alternative fuel today which is packaged in video form due to the Covid-19 pandemic. This research phase begins by collecting the materials needed to make a Rubble BricQ (Rubber Leaf Waste Briquette) video through digital searches (internet). The result of this research is to know how to make Rubble BricQ (Rubber Leaf Waste Briquettes) as an alternative fuel today through video. Therefore, it can be concluded that Rubble BricQ is made by burning rubber leaf waste into charcoal, pounding it until smooth, adding tapioca flour, molding, drying it to dry, and the results can be used immediately.Keywords - Briquettes, Rubber Leaves, Rubble BricQ.